Pengaruh Gaji Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Zailani, Rinawati; Artanto, Andreas Hengki (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
Employees are the main resource in an organization. Organizations will achieve competitive advantage if employees have high performance. This research examines the effect of salary on employee performance by including the job satisfaction variable as a mediating variable. Respondents in this research were 32 people at PT Qolbun Salim Mubarok, using linear regression and hierarchical regression analysis techniques. The results of the analysis show that 1) Salary has a positive and significant effect on employee performance, 2) Salary has a positive and significant effect on job satisfaction, 3) Job satisfaction has a positive and significant effect on employee performance, 4) Job satisfaction partially mediates the effect of salary on employee performance . Based on these results, an organization should pay attention to salary and job satisfaction variables in order to improve performance. If employees feel satisfied at work and have optimal salaries, their performance will be better.